Far from the madding crowd: The molecular basis for immunological escape of plasmodium falciparum (2017)
Like Thomas Hardy’s famous novel Far from the Madding Crowd, Plasmodium falciparum parasites display their most relevant survival structures (proteins) involved in host cell invasion far away from the immune system’s susceptible regions, displaying tremendous genetic variability, to attract the immune response and escape immune pressure. The 3D structure localisation of the conserved amino acid sequences of this deadly parasite’s most relevant proteins involved in host cell invasion, as well as the location of the highly polymorphic, highly immunogenic regions, clearly demonstrates that such structures are far apart, sometimes 90° to 180° opposite, thereby rendering the immune response useless. It is also shown here that these conserved, functionally-relevant structures are immunologically silent, since no immune response has been induced. © 2017, Caister Academic Press. All rights reserved.